Synthesis, characterization and applications of two dimensional nanosheets - Zeng, Zhiyuan (2012)
Graphene has recently sparked great research interest in other type of two dimensional (2D) nanomaterials, such as metal dichalcogenides, which exhibit unique properties that correlate with their size and dimension. However, high-yield production of these single-layer materials from their layered precursors has not been realized with facile and reliable procedures. In the light of this, my aim is to find a new and effective way for high-yield preparation of 2D semiconducting nanosheets and explore their potential application. First, I developed a controllable approach to fabrication of single-layer 2D inorganic nanomaterials, for example, MoS2, WS2, TaS2, TiS2, ZrS2 and graphene, through an electrochemical lithiation process followed by ultrasonication and exfoliation. The Li insertion is precisely controlled in the battery testing platform, and the galvanostaic discharge can be stopped at an appropriate Li amount to prevent decomposition of the lithiated compounds. Particularly, the production of single-layer MoS2 sheets is accomplished with a yield of as high as 92%. The physical and chemical properties of the prepared 2D nanosheets were investigated by XRD, TEM, SEM, AFM, XPS, EDX, Raman, UV and so on. Single-layer MoS2 has a bandgap of 1.8 eV. The field-effect behavior indicates the p-type doping effect of the single-layer MoS2 prepared by our method. As a proof-of-concept application, a single-layer MoS2 based film transistor is fabricated, which is successfully used for sensing of NO with the detection limit of 190 ppt. Our method open a new way for the preparation of 2D nanomaterials with solution-based processability for device applications. Second, through a systematic examination of nanomaterials obtained at different cut-off voltages, we have successfully optimized the electrochemical lithiation conditions and extended this controllable lithiation process into BN, metal selenides and metal tellurides such as NbSe2, WSe2, Sb2Se3 and Bi2Te3. More importantly, we have employed two approaches to improve the quality of the products, i.e., the use of a low discharge current to prevent the high-current induced structure degradation, and the deoxygenation of lithiated compound solutions to alleviate the surface oxidation of the nanosheets during sonication. As a proof-of-concept, the thermoelectric properties of the film sample of NbSe2 nanosheets were tested, which exhibited both the enhanced Seebeck coefficient and electrical conductivity with the p-type semiconducting behavior as compared to the bulk material. Third, two-dimensional materials have great potential in next-generation nanoelectronic devices. As for its application in field-effect transistors (FETs), the use of graphene is restricted because its band gap is zero and it shows semi-metallic property. To open up the band gap of graphene with increased driving current, we prepared large-area graphene nanomesh (GNM) by utilizing anodic aluminum oxide (AAO) as the etching mask, combined with O2 plasma treatment. Through varying the pore size and cell wall thickness of AAO mask, GNM with different neck widths were prepared. Based on field-effect transistor behavior, GNMs exhibited the enhanced p-type semiconducting properties.